Frequency and Functionality: Two Keys for L2 Coursebooks - Alcaraz, Gema (International Journal of English Studies, 2009)
There is no doubt of the importance of vocabulary in EFL coursebooks. Yet, criteria for the selection of target words remain unclear. Frequency and functionality have been proposed as the two underpinning for selection. However, they are usually incompatible so that materials designers must opt for one or the other. The question is which one should be chosen. Despite the fact that recent corpora studies remark the importance of frequency, it seems that functionality still dominates coursebook vocabulary selection.